DINAMIKA PARADIGMA FALAKIYAH NAHDLATUL ULAMA (Ahkam: Jurnal Hukum Islam, 2023)
In determining the beginning of the Hijri month, Nahdlatul Ulama (NU) is known as a user of the rukyah al-hilal method with hisab as a support. However, after NU's 34th congress in Lampung in 2021, NU formulated the concept of qath'iy al-rukyah which is characterized by pure hisab. This shows the dynamics of the NU falakiyah paradigm. This study aims to describe chronologically and historically the dynamics of the NU falakiyah paradigm. The method used in this research is a literature search. The approach used in this research is Thomas S. Kuhn's paradigm theory to analyze how the NU falakiya paradigm develops. The results of this study indicate that in the history of NU, the NU falakiyah paradigm developed dynamically where at its inception there were elements of NU who used pure rukyah (normative paradigm) and some who used pure hisab (rational paradigm). This happens because there is no organizational stipulation to use a certain method in determining the beginning of the Hijri month. In the next period NU decided organizationally to use pure rukyah (normative paradigm), then use rukyah supported by hisab with imkan al-rukyah (normative-rational paradigm) but in certain cases NU used pure hisab with the criteria of qath'iy al-rukyah (paradigm purely rational). The dynamics of the falakiyah paradigm does not only occur organizationally in the NU falakiyah paradigm, but also occurs within the body of NU where there are a group of NU elements who use pure rukyah and also pure hisab which of course is not in accordance with the NU falakiyah paradigm organizationally.